PENGARUH NILAI RELIGIUSITAS DAN PENGETAHUAN PRODUK TERHADAP KEPUTUSAN BOIKOT PRODUK KFC (Studi Pada Konsumen Muslim Bandar Lampung) - Suci Rahmawati (Jurnal Kompetitif Bisnis, 2020)
This research was aimed to find out the effect of religiousity value, and product knowledge towards boycott decision of KFC Product. This type of research applies the quantitative with explanatory approach. The population in this study were Moeslim customer Bandar Lampung. The sampling technique used is purposive sampling which amounted to 100 respondents. Research instrument in this study was a questionnaire who have met the validity anda realibility. Analysis of this research data used linear regression. Based on the results of the research and data analysis, religiosity value and product knowledge has significant effect on the variable of boycott decision. For the next researcher can use others variables that is not included in this research such as halal awareness, ingredient product and social media.